Time Is Running Out'. The Yodel Order and Its Implications for Platform Work in the EU - Aloisi, Antonio (IE University, 2020)
This commentary examinescase C-692/19, an order in response to a request for a preliminary ruling regarding the scope of application of working time protection, handed down by the Court of Justice of the European Union (CJEU) in April 2020.A courier working for a shipping company filed a claimbefore aUKemployment tribunal demanding reclassification as a ‘worker’with accessto the national legislation implementing Directive 2003/88/EC on working time.The tribunal decided to refer the question to the CJEU. At first glance, some elements of the order maygive us the impression that EU working time protection does not cover workerswho may find themselves in a situation of (bogus) self-employment, including those in the platform economy. However, this is not the case. The order is based on a specific set of facts that are in line with the CJEU’s established jurisprudential practiceson the conceptofworker, according towhich workers formally classified as self-employed under the contract or the national law are excluded from the scope of the Working Time Directive only if they enjoy genuine, not nominal organisational autonomy.This analysis is organised as follows. After some introductory remarks, part 2 summarises the arguments of the remitting court and reviews the business model of the delivery company. Part 3 critically discusses some passages of the order. It also examines the notion of ‘worker’ asshaped by the CJEU, highlights strengths and shortcomings of this interpretive attitude, and summarises the proposals to overcome the weaknesses of an under-inclusive and potentially ineffective application of EU law. After appraising the widespread practices in the platform economy and the most recent regulatory developments, part 4 demystifies the issueof organisational flexibility, which is often understood in a unidirectional way, to the advantage of business. This analysisconcludes by advocatingfora purposive adaptionof existing legal categories, beyond the formalistic approach adopted by the referring court in this case.
Keywords: Working time;Concept of 'worker';Platform work;Self employment;Gig economy;Substitution clauses; Working time; Concept of 'worker'; Platform work; Self employment; Gig economy; Substitution clauses; ODS 8 - Trabajo decente y crecimiento económico